VP59 Patients Views On Providing Evidence; Feeding Into The Health Technology Assessment Ecosystem. (2017) - Livingstone, Heidi; Thomas, Lizzie; Leng, Gillian; Kastoryano, Chloe
Abstract : INTRODUCTION: Patient evidence is submitted to the National Institute for Health and Care Excellence (NICE) by patient organizations and individual patient experts. Previously NICE developed a new patient organization evidence submissions template, based on the international HTAi patient submission template for medicines (1). The NICE template was reviewed by surveying committee members and also patient organizations who had used the submission template. The findings were presented at HTAi 2016. The limitation of that review was the low response rate from patient organizations. The key recommendation was to extend the survey to include a larger number of patient organizations. These local findings are an opportunity to contribute to the global Health Technology Assessment (HTA) ecosystem. METHODS: A project group was convened consisting of NICE staff, a committee lay member and a patient organization representative. Together we reassessed the suitability of the previous feedback survey. This was then sent out to patient groups who had completed the submission template from July 2014 to November 2016. Additionally, public involvement staff telephoned selected patient organizations to increase the feedback response rate and gain greater understanding. The anonymized results were shared with patients involved in NICE who helped interpret the results from a patient organization's perspective. RESULTS: Key findings are that patient organizations find: the template clear it was easiest to provide information about living with the condition it was hardest to give information on equality issues and research evidence. They would also like a submission guide, and to receive feedback on their submissions. CONCLUSIONS: Although it was difficult to obtain feedback from the patient organizations on the submission template, the depth of information provided by them was fundamental to updating the template and producing a supporting guide. This feedback on the local English needs can be used when evaluating the international submission template to form a greater part of the HTA ecosystem.